Personal Selling Done by Raffles Hotel Jakarta’s Salespersons - Wibawa, Idham Sakti; Fajri, Ilham; Faturrahman, Azhali Cendra (Universitas Indonesia Membangun (Inaba), 2024)
Personal selling remains a fundamental aspect of modern marketing strategies, particularly in the hospitality industry. This study examines the nuanced techniques employed by salespersons at Raffles Jakarta, a renowned luxury hotel, to effectively engage potential clients and drive sales. Through qualitative analysis, including interviews and observations, the study explores the personalized approaches, relationship-building tactics, and adaptability demonstrated by Raffles Jakarta's sales team. Findings reveal the significance of tailoring sales pitches to individual client preferences, leveraging interpersonal skills to establish trust and rapport, and the importance of continuous adaptation to evolving market dynamics. Insights gleaned from this study contribute to a deeper understanding of effective personal selling practices within the context of upscale hospitality, offering valuable implications for both practitioners and researchers in the field of sales and marketing.